High‐Performance Yolk‐Shell Structured Silicon‐Carbon Composite Anode Preparation via One‐Step Gas‐Phase Deposition and Etching Technique - Zhou, Peng; Xiao, Peng; Pang, Liang; Jiang, Ziang; Hao, Ming; Li, Yang; Wu, Feixiang (Advanced functional materials, 2025)
For producing high‐capacity silicon (Si) anodes, a combined gas‐phase deposition and etching technique is developed to construct yolk‐shell structured silicon‐carbon composites. As a novel etching agent in battery field, NF3 is applied to selectively etch Si to tailor the architecture. Si particles as self‐sacrificed precursor have no need to build artificial or complex templates in advance, thereby greatly simplifying fabrication process and showcasing practicality. As a result, yolk‐shell structured silicon‐carbon composites are successfully fabricated in a single step. Sufficient buffer space between Si and carbon layer accommodates the significant expansion of Si during lithiation, preventing fracture of the carbon layer, which greatly improves service life of Si‐based anodes. Moreover, the refined particle size of Si and abundant pores in inner Si cores enhance the lithiation and de‐lithiation kinetic. Even with a high Si loading of 3.9 mg cm−2, the produced anode exhibits a superior areal capacity of 16.3 mAh cm−2 at 0.2 mA cm−2. Furthermore, at a high current density of 4 A g−1, it demonstrates an excellent capacity of 1114 mAh g−1 after 1000 cycles with a capacity retention of 96.3%. Additionally, with pre‐lithiation, it is successfully paired with an iron trifluoride cathode to construct high‐energy lithium‐ion batteries. The yolk‐shell structured silicon‐carbon composites are fabricated in a single step by combining chemical vapor deposition method and gas‐phase etching technology without the need for additional templates. Sufficient buffer space between Si particles and the carbon layer accommodates the significant expansion of silicon during lithiation, preventing any fracture of the carbon layer, which greatly improves service life of Si‐based anodes.